2014
DOI: 10.1371/journal.pone.0107703
|View full text |Cite
|
Sign up to set email alerts
|

Guava Leaf Extract Inhibits Quorum-Sensing and Chromobacterium violaceum Induced Lysis of Human Hepatoma Cells: Whole Transcriptome Analysis Reveals Differential Gene Expression

Abstract: Quorum sensing (QS) is a process mediated via small molecules termed autoinducers (AI) that allow bacteria to respond and adjust according to the cell population density by altering the expression of multitudinous genes. Since QS governs numerous bioprocesses in bacteria, including virulence, its inhibition promises to be an ideal target for the development of novel therapeutics. We found that the aqueous leaf extract of Psidium guajava (GLE) exhibited anti-QS properties as evidenced by inhibition of violacein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…There may be some more phytochemicals (remained in the GCMS data beyond the known ones) in LFE which are yet to be identified as hepatoprotective agents. In one of our previous reports, it was shown that multiple constituents of a PPE may act synergistically or additively to affect the biological system [57]. There are also other reports on using combination of compounds to gain higher therapeutic effectiveness over singly administered compound(s) [58].…”
Section: Discussionmentioning
confidence: 99%
“…There may be some more phytochemicals (remained in the GCMS data beyond the known ones) in LFE which are yet to be identified as hepatoprotective agents. In one of our previous reports, it was shown that multiple constituents of a PPE may act synergistically or additively to affect the biological system [57]. There are also other reports on using combination of compounds to gain higher therapeutic effectiveness over singly administered compound(s) [58].…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, guava leaf extract was demonstrated to have similar dose‐dependent inhibition of violacein production without affecting the growth of C. violaceum (Ghosh et al . ). Moreover, genome‐wide transcriptome analyses of C. violaceum cells grown in the presence and absence of guava leaf extract have revealed a panel of QS‐controlled genes, including the virulence factors (Ghosh et al .…”
Section: Resultsmentioning
confidence: 97%
“…Applying simple biotechnological approaches in combination to Ayurveda, we have been able to decipher mechanisms of action of plant drugs in single form [24][25][26][27] or poly herbal fermented preparation, which not only became able to inhibit biofilm formation of Pseudomonas aeruginosa, or restrict quorum sensing of Chomobacterium violaceum, but also significantly inhibited several natural isolates found to possess resistance towards different classes of conventional antibiotic drugs. Attempts have been made to check the activity of this Ayurveda based drug against various kinds of enteropathogenic metallo beta lactamase producing organisms, and to identify probable mechanisms of action(s) with the help of standard scientific methodology currently adapted in pharmaceutical industry and laboratories across the globe.…”
Section: Discussionmentioning
confidence: 99%